Responsabilidade social e turismo: a relação entre a comunidade e a rede de resorts Vila Galé no nordeste brasileiro. - Machado, Suellen Barbosa (2019)
At the end of the 20th century, tourism became one of the most important activities in the world. Routes began to be drawn, distances seemed to be shortened. With the evolution of the means of transportation, the equipment of lodging became more and more specialized in the search for a good experience to the tourist. On the other hand, in discovering the paradisiacal scenery of a destination, there was a trail of destruction of nature, with irregular constructions, grounded watercourses, pollution, besides being able to be remade because it does not seem an essential element of a stay of a tourist. Against this backdrop, Social Responsibility started to integrate public domains in Brazil, driven by ISO 26000, which regulates it and defines it as corporate behavior that integrates social and environmental elements that are not necessarily contained in legislation, but which meet the expectations of the society in relation to the company. That is, companies must leave a continuous legacy for the communities in which they are inserted and their future generations. In this sense, the research in question focuses on the investigation of Social Responsibility in the network of Vila Galé resorts in three projects of the northeastern coast, being located in Cumbuco-CE, Guarajuba-BA and Cabo de Santo Agostinho-PE, aiming to demonstrate the actions of social responsibility of the enterprises and the satisfaction of the communities before them, in each municipality investigated and in a more specific way identify similarities and differences in the company's social responsibility in the three different states, evaluate if the actions carried out are coherent with the needs and realities of the communities and finally, understand the possibilities for improvements in socio-environmental practices based on the situations encountered. For this, the research was built on a qualitative approach of a historical and structural nature, which makes it possible to identify the causes and consequences of the problems, their contradictions, relations, qualities and quantitative dimensions for the understanding of reality, by conducting semi-structural interviews with the management of each enterprise and community to its surroundings that ended up noting that although social responsibility is widely diffused, it is not yet fully supervised, still being far below the needs and expectations of the Community. It was also verified that the actions expended to the community are not uniform in the localities, and there are distinctions in the practices of actions that end in constructing more sustainable tourism.